Evidence of localized resource depletion following a natural colonization event by a large marine predator. (4th March 2014) - Kuhn, Carey E.; Baker, Jason D.; Towell, Rodney G.; Ream, Rolf R.; Hays, Graeme
Summary For central place foragers, forming colonies can lead to extensive competition for prey around breeding areas and a zone of local prey depletion. As populations grow, this area of reduced prey can expand impacting foraging success and forcing animals to alter foraging behaviour. Here, we examine a population of marine predators, the northern fur seal (Callorhinus ursinus), which colonized a recently formed volcanic island, and assess changes in foraging behaviour associated with increasing population density. Specifically, we measured pup production and adult foraging behaviour over a 15‐year period, during which the population increased 4‐fold. Using measures of at‐sea movements and dive behaviour, we found clear evidence that as the population expanded, animals were required to allot increasing effort to obtain resources. These changes in behaviour included longer duration foraging trips, farther distances travelled, a larger foraging range surrounding the island and deeper maximum dives. Our results suggest that as the northern fur seal population increased, local prey resources were depleted as a result of increased intraspecific competition. In addition, the recent slowing of population growth indicates that this population may be approaching carrying capacity just 31 years after a natural colonization event. Our study offers insight into the dynamics of population growth and impacts of increasing population density on a large marine predator. Such data could be vital for understanding future population fluctuations that occur in response to the dynamic environment, as natural and anthropogenic factors continue to modify marine habitats.